Dry-method pole piece mixed with large and small particles and preparation method thereof

By using a dry electrode sheet preparation method with mixed particles of large and small particles in the energy storage positive electrode material, the problems of low electronic conductivity, low lithium ion diffusion coefficient, low compaction density and low energy density in the prior art are solved, and the electrode sheet with high compaction density and excellent conductivity are achieved, which improves the energy density of the battery and simplifies the process.

CN119542349APending Publication Date: 2025-02-28ZHUHAI KECHUANG LITHIUM BATTERY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411849918.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

In the preparation of energy storage positive electrode materials, the prior art cannot solve the problems of low electron conductivity, low lithium ion diffusion coefficient, low compaction density and low energy density at the same time.

Method used

The dry-metal sheet preparation method is adopted for mixing large and small-particle active substances, and evenly mixing them with conductive agents and binders, hot rolling and multiple rolling are carried out to form a high-pressure density dry-metal diaphragm, and finally obtain high-performance dry-metal sheets through thermal overlay.

Benefits of technology

The high compaction density and excellent conductivity of the electrode sheet are achieved, the energy density of the battery is improved, the problems of low compaction density and poor conductivity caused by particle agglomeration are overcome, and the process is simplified and industrial effectiveness is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542349A_ABST
    Figure CN119542349A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a dry-method pole piece mixed with large and small particles and a preparation method of the dry-method pole piece. Active particles with different particle sizes are mixed and form a film by using a dry process, on one hand, due to a unique fiber net structure of a dry process, the mixed particles can be anchored in position, and non-uniformity caused by movement of the particles is avoided; on the other hand, the compaction of the pole piece and the energy density of the battery can be improved by mixing large and small particles, and the performance is complementary; meanwhile, the mixing of the particles enables the contact of the active substances to be tighter, and the conductivity of the electrode is more excellent; and the high-performance and stable pole piece is constructed by virtue of structural maintenance of the fibers which are formed by mutually mixing large and small particles and crisscrossed fibers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and more specifically, to a dry-process electrode sheet with large and small particles mixed and a preparation method thereof. Background Art

[0002] The cathode materials currently used in energy storage (such as lithium iron phosphate, sodium iron pyrophosphate) have attracted widespread attention due to their long service life, high safety, low price, and environmental friendliness. However, while meeting the energy storage requirements, there are also disadvantages that limit their further commercial application. One is the low electronic conductivity and lithium ion diffusion coefficient at room temperature. The other is the low volumetric specific energy due to low compaction density. A series of measures such as doping, morphology control, carbon coating, and size reduction are currently used to overcome these shortcomings. However, so far, some methods have not been widely used due to complex processes. Considering industrial utility, a simple, practical, and efficient method is of great significance. The physical mixing method has recently attracted attention due to its simplicity, ease of operation, and mature technology.

[0003] Energy storage cathode materials with small particle size have better low temperature performance, rate performance and conductivity due to their high surface area, short diffusion length and fast kinetics. However, there are also some adverse effects. For example, a larger surface area may lead to severe oxidation of the electrolyte on the electrode surface, poor processability, and low compaction density caused by particle agglomeration. Energy storage cathode materials with large particle size have higher compaction density and energy density, low price and easier processing.

[0004] It can be seen from this that when the existing process uses pure large-particle active materials or pure small-particle active materials to prepare electrodes, their respective defects cannot be avoided. Summary of the invention

[0005] In order to address the deficiencies of the prior art, the present invention aims to combine the advantages of large and small particle materials, use a large and small particle blending method to develop a high-density, high-performance electrode, and construct a completely new electrode structure through a dry electrode process.

[0006] To achieve the above object, the present invention adopts the following technical solution: A method for preparing a dry-process electrode with mixed large and small particles comprises the following steps: S1: mixing large particle active substance and small particle active substance uniformly to obtain a first mixed material; S2: uniformly mixing the first mixed material and the conductive agent to obtain a second mixed material; S3: uniformly mixing the second mixed material with the binder to obtain a third mixed material; S4: screening the third mixed material and subjecting it to hot roller pressing, and obtaining a dry film after multiple rolling; S5: thermally laminating the dry process membrane sheet and the current collector by rollers to obtain a dry process electrode sheet; S6: Roll the dry electrode sheet through a roller press to a suitable compaction density to obtain a dry electrode sheet.

[0007] Preferably, the large particle active material and the small particle active material are both selected from any one of lithium iron phosphate, sodium iron pyrophosphate, ternary materials, layered oxides, Prussian blue, Prussian white, graphite or hard carbon.

[0008] Preferably, the particle size of the large particle active substance is 1-20 microns, and the particle size of the small particle active substance is 0.1-1 microns.

[0009] Preferably, the particle size ratio of large active substance particles to small active substance particles is >3.

[0010] Preferably, the conductive agent is selected from any one of SP, acetylene black, carbon nanotubes, carbon fibers or graphene.

[0011] Preferably, the binder is selected from any one of polytetrafluoroethylene, polyvinylidene fluoride, CMC, PE, PEO or polyacrylonitrile.

[0012] Preferably, the thermal bonding temperature of the dry process membrane and the current collector is 120-200°C.

[0013] Preferably, the weight ratio of large particle active material, small particle active material, conductive agent and binder is (140-150):(42-52):(2-6):(2-6).

[0014] The present invention also provides another method for preparing a dry-process electrode with mixed large and small particles, which comprises the following steps: S1: uniformly mixing the large particle active material with a part of the conductive agent to obtain a first coarse particle mixed material, and uniformly mixing the small particle active material with the remaining conductive agent to obtain a first small particle mixed material; S2: uniformly mixing the first coarse particle mixture material with a portion of the binder to obtain a second coarse particle mixture material, and uniformly mixing the first small particle mixture material with the remaining binder to obtain a second small particle mixture material; S3: screening the second coarse particle mixture material and hot rolling it, and obtaining a large particle dry process membrane sheet through multiple rolling; screening the second coarse and small particle mixture material and hot rolling it, and obtaining a small particle dry process membrane sheet through multiple rolling; S4: stacking and calendering the large-particle dry-process membrane sheet and the small-particle dry-process membrane sheet, so that the small-particle active material is embedded in the large-particle active material to obtain a dry-process membrane sheet; S5: thermally laminating the dry process membrane sheet and the current collector by rollers to obtain a dry process electrode sheet; S6: Roll the dry electrode sheet through a roller press to a suitable compaction density to obtain a dry electrode sheet.

[0015] Compared with the previous preparation method, this preparation method only changes the mixing order of the raw materials, and the raw material composition remains unchanged.

[0016] Another object of the present invention is to provide a dry electrode plate, which is prepared by any one of the two preparation methods mentioned above.

[0017] The present application has the following beneficial effects: active particles of different particle sizes are mixed and film-formed using a dry process. On the one hand, due to the unique fiber mesh structure of the dry process, the mixed particles can be anchored in position to avoid unevenness caused by the movement of the particles; on the other hand, the blending of large and small particles can improve the compaction of the electrode and the energy density of the battery, and the performance is complementary; at the same time, the blending of particles makes the contact of the active material closer and the electrode conductivity is also better; large and small particles are mixed and the criss-crossed fibers maintain the structure to construct a high-performance and stable electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a structural diagram of the dry-process electrode in the present invention. DETAILED DESCRIPTION

[0019] The present application is further described in detail below with reference to the accompanying drawings and embodiments. Example 1

[0020] The raw materials for the preparation of this embodiment are 4g of dispersed polytetrafluoroethylene powder, 4g of conductive carbon black SP, 144g of large-particle lithium iron phosphate, and 48g of small-particle lithium iron phosphate. Among them, the particle size of the large-particle lithium iron phosphate is 1-20 microns, the particle size of the small-particle lithium iron phosphate is 0.1-1 microns, and the particle size ratio of the large-particle lithium iron phosphate to the small-particle lithium iron phosphate is >3.

[0021] The preparation method of the dry-process electrode with mixed large and small particles in this embodiment includes the following steps: S1: mixing large-particle lithium iron phosphate and small-particle lithium iron phosphate uniformly at a low speed to obtain a first mixed material; S2: mixing the first mixed material with the conductive carbon black SP at a low speed to obtain a second mixed material; S3: mixing the second mixed material with the binder PTFE and shearing at high speed to obtain a third mixed material; S4: screening the third mixed material and subjecting it to hot roller pressing to obtain a dry film through multiple rolling processes; S5: The dry process membrane sheet and the current collector are thermally laminated by a roller to obtain a dry process electrode sheet, wherein the thermal lamination temperature is 150±5°C; S6: Roll the dry electrode sheet through a roller press to a suitable compaction density to obtain a dry electrode sheet. Example 2

[0022] The raw materials for the preparation of this embodiment are 4g of dispersed polytetrafluoroethylene powder, 4g of conductive carbon black SP, 144g of large-particle lithium iron phosphate, and 48g of small-particle lithium iron phosphate. Among them, the particle size of the large-particle lithium iron phosphate is 1-20 microns, the particle size of the small-particle lithium iron phosphate is 0.1-1 microns, and the particle size ratio of the large-particle lithium iron phosphate to the small-particle lithium iron phosphate is >3.

[0023] The preparation method of the dry-process electrode with mixed large and small particles in this embodiment includes the following steps: S1: uniformly mix all the large-particle lithium iron phosphate and 3g of conductive carbon black SP to obtain a first coarse-particle mixed material, and uniformly mix all the small-particle lithium iron phosphate and 1g of conductive carbon black SP to obtain a first small-particle mixed material; S2: the first coarse particle mixture material is mixed with 3 g of binder PTFE to obtain a second coarse particle mixture material, and the first small particle mixture material is mixed with 1 g of binder PTFE to obtain a second small particle mixture material; S3: screening the second coarse particle mixture material and hot rolling it, and obtaining a large particle dry process membrane sheet through multiple rolling; screening the second coarse and small particle mixture material and hot rolling it, and obtaining a small particle dry process membrane sheet through multiple rolling; S4: stacking and calendering the large-particle dry-process membrane sheet and the small-particle dry-process membrane sheet, so that the small-particle active material is embedded in the large-particle active material to obtain a dry-process membrane sheet; S5: The dry process membrane sheet and the current collector are thermally laminated by a roller to obtain a dry process electrode sheet, wherein the thermal lamination temperature is 150±5°C; S6: Roll the dry electrode sheet through a roller press to a suitable compaction density to obtain a dry electrode sheet. Example 3

[0024] The raw materials for the preparation of this embodiment are 4g of dispersed polytetrafluoroethylene powder, 4g of conductive carbon black SP, 140g of large-particle lithium iron phosphate, and 52g of small-particle lithium iron phosphate. Among them, the particle size of the large-particle lithium iron phosphate is 1-20 microns, the particle size of the small-particle lithium iron phosphate is 0.1-1 microns, and the particle size ratio of the large-particle lithium iron phosphate to the small-particle lithium iron phosphate is >3.

[0025] The preparation method of the dry-process electrode with a mixture of large and small particles in this embodiment is the same as that in Example 1. Example 4

[0026] The raw materials for the preparation of this embodiment are 4g of dispersed polytetrafluoroethylene powder, 4g of conductive carbon black SP, 150g of large-particle lithium iron phosphate, and 42g of small-particle lithium iron phosphate. Among them, the particle size of the large-particle lithium iron phosphate is 1-20 microns, the particle size of the small-particle lithium iron phosphate is 0.1-1 microns, and the particle size ratio of the large-particle lithium iron phosphate to the small-particle lithium iron phosphate is >3.

[0027] The preparation method of the dry-process electrode with a mixture of large and small particles in this embodiment is the same as that in Example 1. Example 5

[0028] The raw materials for the preparation of this embodiment are 4g of dispersed polytetrafluoroethylene powder, 4g of conductive carbon black SP, 140g of large-particle lithium iron phosphate, and 52g of small-particle lithium iron phosphate. Among them, the particle size of the large-particle lithium iron phosphate is 1-20 microns, the particle size of the small-particle lithium iron phosphate is 0.1-1 microns, and the particle size ratio of the large-particle lithium iron phosphate to the small-particle lithium iron phosphate is >3.

[0029] The preparation method of the dry-process electrode with a mixture of large and small particles in this embodiment is the same as that in Example 2. Example 6

[0030] The raw materials for the preparation of this embodiment are 4g of dispersed polytetrafluoroethylene powder, 4g of conductive carbon black SP, 150g of large-particle lithium iron phosphate, and 42g of small-particle lithium iron phosphate. Among them, the particle size of the large-particle lithium iron phosphate is 1-20 microns, the particle size of the small-particle lithium iron phosphate is 0.1-1 microns, and the particle size ratio of the large-particle lithium iron phosphate to the small-particle lithium iron phosphate is >3.

[0031] The preparation method of the dry-process electrode with a mixture of large and small particles in this embodiment is the same as that in Example 2. Example 7

[0032] The raw materials for the preparation of this embodiment are 4g of binder styrene butadiene rubber (SBR), 4g of conductive carbon black SP, 144g of large-particle graphite powder, and 48g of small-particle graphite powder. The particle size of the large-particle graphite powder is 1-20 microns, the particle size of the small-particle graphite powder is 0.1-1 microns, and the particle size ratio of the large-particle graphite powder to the small-particle graphite powder is >3.

[0033] The preparation method of the dry-process electrode with mixed large and small particles in this embodiment includes the following steps: S1: mixing large-grain graphite powder and small-grain graphite powder uniformly at a low speed to obtain a first mixed material; S2: mixing the first mixed material with the conductive carbon black SP at a low speed to obtain a second mixed material; S3: mixing the second mixed material with the binder SBR and subjecting the mixture to high-speed shearing to obtain a third mixed material; S4: screening the third mixed material and subjecting it to hot roller pressing to obtain a dry film through multiple rolling processes; S5: The dry process membrane sheet and the current collector are thermally laminated by rollers to obtain a dry process electrode sheet, wherein the thermal lamination temperature is 80±5°C; S6: Roll the dry electrode sheet through a roller press to a suitable compaction density to obtain a dry electrode sheet.

[0034] Comparative Example 1 The raw materials for preparation in this embodiment are 4g of polyvinylidene fluoride powder, 4g of conductive carbon black SP, 192g of large-particle lithium iron phosphate, and an appropriate amount of NMP (N-methylpyrrolidone), wherein the particle size of the large-particle lithium iron phosphate is 1-20 microns.

[0035] The preparation method of the dry-process electrode of this comparative example comprises the following steps: S1: Mixing polyvinylidene fluoride powder and NMP for 4 hours to obtain a first mixture; S2: adding the conductive carbon black SP to the first mixture and mixing for 4 hours to obtain a second mixture; S3: adding large-particle lithium iron phosphate to the second mixture, mixing at a low speed for 5 hours, and then mixing at a high speed for 3 hours to obtain an electrode slurry, and controlling the final slurry solid content to 55%; S4: coating the electrode slurry on the current collector through a coating and drying machine to obtain a wet electrode sheet; S5: Roll the electrode sheet through a roller press to a suitable compaction density to obtain an electrode sheet.

[0036] Comparative Example 2 The raw materials for preparation in this embodiment are 4g of polyvinylidene fluoride powder, 4g of conductive carbon black SP, 192g of small-particle lithium iron phosphate, and an appropriate amount of NMP. The particle size of the small-particle lithium iron phosphate is 0.1-1 micron.

[0037] The preparation method of the dry-process electrode of this comparative example comprises the following steps: S1: Mixing polyvinylidene fluoride powder and NMP for 4 hours to obtain a first mixture; S2: adding the conductive carbon black SP to the first mixture and mixing for 4 hours to obtain a second mixture; S3: adding large-particle lithium iron phosphate to the second mixture, mixing at a low speed for 5 hours, and then mixing at a high speed for 3 hours to obtain an electrode slurry, and controlling the final slurry solid content to 55%; S4: coating the electrode slurry on the current collector through a coating and drying machine to obtain a wet electrode sheet; S5: Roll the electrode sheet through a roller press to a suitable compaction density to obtain an electrode sheet.

[0038] Comparative Example 3 The raw materials for the preparation of this comparative example are 4g of polyvinylidene fluoride powder, 4g of conductive carbon black SP, 144g of large-particle lithium iron phosphate, 48g of small-particle lithium iron phosphate, and an appropriate amount of NMP. Among them, the particle size of the large-particle lithium iron phosphate is 1-20 microns, the particle size of the small-particle lithium iron phosphate is 0.1-1 microns, and the particle size ratio of the large-particle lithium iron phosphate to the small-particle large-particle lithium iron phosphate is >3.

[0039] The preparation method of the dry-process electrode of this comparative example comprises the following steps: S1: Mixing polyvinylidene fluoride powder and NMP for 4 hours to obtain a first mixture; S2: adding the conductive carbon black SP to the first mixture and mixing for 4 hours to obtain a second mixture; S3: adding large-particle lithium iron phosphate to the second mixture, mixing at a low speed for 5 hours, and then mixing at a high speed for 3 hours to obtain an electrode slurry, and controlling the final slurry solid content to 55%; S4: coating the electrode slurry on the current collector through a coating and drying machine to obtain a wet electrode sheet; S5: Roll the electrode sheet through a roller press to a suitable compaction density to obtain an electrode sheet.

[0040] Comparative Example 4 The raw materials for preparing this comparative example are 4g of styrene-butadiene rubber (SBR), 4g of conductive carbon black SP, 192g of large-particle graphite powder, and an appropriate amount of thickener sodium carboxymethyl cellulose (CMC). The particle size of the large-particle graphite powder is 1-20 microns.

[0041] The preparation method of the dry-process electrode sheet of this comparative example is: prepare the above raw materials into negative electrode slurry, apply the negative electrode slurry on the current collector through a coating dryer to obtain an electrode sheet, and roll the electrode sheet to a suitable compaction density through a roller press to obtain an electrode electrode sheet.

[0042] Comparative Example 5 The raw materials for the preparation of this comparative example are 4g of styrene-butadiene rubber (SBR), 4g of conductive carbon black SP, 192g of small-particle graphite powder, and an appropriate amount of thickener sodium carboxymethyl cellulose (CMC). Among them, the particle size of the small-particle lithium iron phosphate is 0.1-1 micron.

[0043] The preparation method of the dry-process electrode sheet of this comparative example is: prepare the above raw materials into negative electrode slurry, apply the negative electrode slurry on the current collector through a coating dryer to obtain an electrode sheet, and roll the electrode sheet to a suitable compaction density through a roller press to obtain an electrode electrode sheet.

[0044] The compaction density and internal resistance of the pole pieces prepared in Examples 1-7 and Comparative Examples 1-5 were tested respectively, and the results are shown in Table 1: Table 1 Pole piece physical properties test table Group <![CDATA[Compaction density (g / cm 3 )]]> Electrode resistivity (Ω*cm) Example 1 2.61 250 Example 2 2.60 270 Example 3 2.58 242 Example 4 2.64 265 Example 5 2.56 258 Example 6 2.72 290 Example 7 1.86 0.53 Comparative Example 1 2.45 1490 Comparative Example 2 2.39 1530 Comparative Example 3 2.46 1410 Comparative Example 4 1.75 0.79 Comparative Example 5 1.62 0.86 Comparing the data of Examples 1-6 and Comparative Examples 1-3, it can be seen that the use of a mixture of large and small particle active substances and a dry process in the positive electrode raw material system to prepare the positive electrode can improve the compaction density and conductivity of the positive electrode. Comparing the data of Example 7 and Comparative Examples 4-5, it can be seen that the use of a mixture of large and small particle active substances and a dry process in the negative electrode raw material system to prepare the negative electrode can also improve the compaction density and conductivity of the negative electrode. Comparing the data of Example 1 and Examples 3-4, it can be seen that increasing the proportion of large particle active substances can increase the compaction density of the electrode, and increasing the proportion of small particle active substances can reduce the resistivity of the electrode. Comparing the data of Example 2 and Examples 5-6, it is once again confirmed that increasing the proportion of large particle active substances can increase the compaction density of the electrode, and increasing the proportion of small particle active substances can reduce the resistivity of the electrode.

[0045] In summary, the present invention uses a dry process to mix active particles of different particle sizes and form a film. On the one hand, due to the unique fiber mesh structure of the dry process, the mixed particles can be anchored in position to avoid uneven movement of the particles; on the other hand, the mixing of large and small particles can improve the compaction of the electrode and the energy density of the battery, and the performance is complementary; at the same time, the mixing of particles makes the contact of the active material closer, and the electrode conductivity is also better; the large and small particles are mixed and the criss-crossed fibers maintain the structure to construct a high-performance and stable electrode. In addition, because the wet slurry system is difficult to overcome the influence of gravity, the dry preparation of the present invention also overcomes the problem of uneven coating caused by the stratification of large and small particles when using the wet method to mix large and small particles.

[0046] The above specific embodiments are merely explanations of the present application and are not limitations of the present application. After reading this specification, those skilled in the art may make modifications to the embodiments without any creative contribution as needed. However, as long as they are within the scope of the claims of the present application, they are protected by the patent law.

Claims

1. A method for preparing a dry-process electrode with mixed large and small particles, characterized in that: The following steps are involved: S1: mixing large particle active substance and small particle active substance uniformly to obtain a first mixed material; S2: uniformly mixing the first mixed material and the conductive agent to obtain a second mixed material; S3: uniformly mixing the second mixed material with the binder to obtain a third mixed material; S4: screening the third mixed material and subjecting it to hot roller pressing, and obtaining a dry film after multiple rolling; S5: thermally laminating the dry process membrane sheet and the current collector by rollers to obtain a dry process electrode sheet; S6: Roll the dry electrode sheet through a roller press to a suitable compaction density to obtain a dry electrode sheet.

2. The method for preparing a dry-process electrode with a mixture of large and small particles according to claim 1, characterized in that: The large particle active material and the small particle active material are both selected from any one of lithium iron phosphate, sodium iron pyrophosphate, ternary materials, layered oxides, Prussian blue, Prussian white, graphite or hard carbon.

3. The method for preparing a dry-process electrode with a mixture of large and small particles according to claim 1, characterized in that: The particle size of the large particle active substance is 1-20 microns, and the particle size of the small particle active substance is 0.1-1 microns.

4. The method for preparing a dry-process electrode with mixed large and small particles according to claim 3, characterized in that: The particle size ratio of large particle active substance to small particle active substance is greater than 3.

5. The method for preparing a dry-process electrode with mixed large and small particles according to claim 1, characterized in that: The conductive agent is selected from any one of SP, acetylene black, carbon nanotubes, carbon fibers or graphene.

6. The method for preparing a dry-process electrode with mixed large and small particles according to claim 1, characterized in that: The binder is selected from any one of polytetrafluoroethylene, polyvinylidene fluoride, CMC, PE, PEO or polyacrylonitrile.

7. The method for preparing a dry-process electrode with mixed large and small particles according to claim 1, characterized in that: The thermal bonding temperature of the dry process membrane and the current collector is 80-200°C.

8. The method for preparing a dry-process electrode with mixed large and small particles according to claim 1, characterized in that: The weight ratio of large particle active material, small particle active material, conductive agent and binder is (140-150):(42-52):(2-6):(2-6).

9. A method for preparing a dry-process electrode with mixed large and small particles, characterized in that: The following steps are involved: S1: uniformly mixing the large particle active material with a part of the conductive agent to obtain a first coarse particle mixed material, and uniformly mixing the small particle active material with the remaining conductive agent to obtain a first small particle mixed material; S2: uniformly mixing the first coarse particle mixture material with a portion of the binder to obtain a second coarse particle mixture material, and uniformly mixing the first small particle mixture material with the remaining binder to obtain a second small particle mixture material; S3: screening the second coarse particle mixture material and hot rolling it, and obtaining a large particle dry process membrane sheet through multiple rolling; screening the second coarse and small particle mixture material and hot rolling it, and obtaining a small particle dry process membrane sheet through multiple rolling; S4: stacking and calendering the large-particle dry-process membrane sheet and the small-particle dry-process membrane sheet, so that the small-particle active material is embedded in the large-particle active material to obtain a dry-process membrane sheet; S5: thermally laminating the dry process membrane sheet and the current collector by rollers to obtain a dry process electrode sheet; S6: Roll the dry electrode sheet through a roller press to a suitable compaction density to obtain a dry electrode sheet.

10. A dry-process electrode with mixed large and small particles, characterized in that: The invention is prepared by the method for preparing a dry-process electrode with a mixture of large and small particles as described in any one of claims 1 to 9.